The Expressions Of Ngalem In The Javanese Society In Kebumen Regency - Purwaningrum, Prapti Wigati; Harmoko, Danang Dwi; Wibowo, Ary Iswanto; Nisa, Baiatun (LPPM Universitas Bina Sarana Informatika, 2024)
This research is based on the use of